2020
DOI: 10.1002/pchj.362
|View full text |Cite
|
Sign up to set email alerts
|

Fluid compensation in response to disappearance of the meaning of work

Abstract: This study examined one's compensatory response to the sudden disappearance of the meaning of work. In a lab experiment, the unexpected termination of a preceding task was found to enhance one's labor supply in an irrelevant ensuing task, which provided direct support for one's pursuit of meaning and the fluid compensation strategy proposed by the Meaning Maintenance Model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
(8 reference statements)
1
11
0
Order By: Relevance
“…Since all the experimental data went lost, and they were not allowed to redo the experiment for time concern, the meaning of work could not be restored in the current experimental task. However, they could put their hearts and soul into the following experimental task so as to restore the meaning of participating in our experiments (Meng and Ouyang, 2020), which was exactly what we found in this study.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Since all the experimental data went lost, and they were not allowed to redo the experiment for time concern, the meaning of work could not be restored in the current experimental task. However, they could put their hearts and soul into the following experimental task so as to restore the meaning of participating in our experiments (Meng and Ouyang, 2020), which was exactly what we found in this study.…”
Section: Discussionsupporting
confidence: 74%
“…In addition, while the unexpected termination of a work project is a small probability event, it is much more common that employees have to work on a meaningless work project in the first place. In this situation, a compensation effect induced by meaningless work may take place as well, as certain psychological and behavioral strategies (e.g., to work on something more meaningful) may be adopted to compensate for the insufficiency of meaning (Meng and Ouyang, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies mainly examined effects of contextual factors and characteristics of the task itself on one's autonomous motivation (Deci and Ryan, 1985b;Bergin, 1999;Deci and Ryan, 2000;Gagné, 2014), our findings suggested that actually there are interplays between prior experience and one's motivation in the current activity. As it is a commonplace that a person would take part in several activities in a row, researchers may pay more attention to these dynamics and examine other influencing factors of one's motivation from an intertemporal perspective (Meng and Ouyang, 2020;Newton et al, 2020;Wei et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Intrinsic motivation is typically defined as the performing of an activity out of interest, curiousness and enjoyment (Deci and Ryan, 1985b). As a broader construct that encompasses intrinsic motivation, autonomous motivation describes one's willingness and volition based on either values or interests (Hagger and Chatzisarantis, 2016;Kuvaas et al, 2016;Meng and Ouyang, 2020). Previous studies have consistently suggested one's autonomous motivation level to be a crucial factor in affecting job performance, innovative behaviors, work engagement as well as academic attainment (Guo et al, 2014;Nunez and Leon, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…If used in a proper manner, competition can be a powerful motivator, which can effectively strengthen both autonomous and controlled motivation. While autonomous motivation refers to one’s natural tendency to be curious and interested, to look for challenges and develop skills and knowledge without external incentives ( Hagger and Chatzisarantis, 2016 ; Meng and Ouyang, 2020 ), controlled motivation describes one’s engagement in an activity with the aim of attaining a reward or avoiding a punishment ( Ryan and Deci, 2017 ). In sports tournaments, athletes are highly motivated to outperform others and to win a prize, in which case the athletes are externally driven.…”
Section: Introductionmentioning
confidence: 99%